Analisis Studi Kelayakan Bisnis Usaha Kedai Es Coklat - Dzaki, Hilmi; Abadi, Muhammad Taufik (BISMA : Business and Management Journal, 2023)
Talking aboutthe culinary business is certainly an interesting discussion to review. Thereason is, the culinary world which is closely related to the human need for drinks is certainly a business opportunity that never dies.One of the culinary businesses in the beverage sector is chocolate ice. The purpose of this study is to analyze the feasibility of the business at the chocolate ice shop. This research method was conducted using a qualitative approach. The location for selecting the chocolate ice shop coincided with Pak Han's ice chocolate shop, Kajen square. The results showed that the analysis of market, competitor and marketing mix aspects showed that the business prospects for the chocolate ice shop were very good, with a cheap price of IDR 6,000.00 + breadof IDR 1,000.00, you can enjoy this fresh drink. This can be seen from the chocolate ice enthusiasts where until now the seller can make a profit of IDR 5,000,000.00/month. By selling on the roadside of the Kajen Square, it is a strategy to increase marketingand expand the market share network